WATER DEFICIT ENSURES THE PHOTOCHEMICAL EFFICIENCY OF Copaifera langsdorffii Desf - Rodrigues, Angelica Lino [UNESP]; Lima, Liane; Schley, Thayssa Rabelo [UNESP]; Rolim de Almeida, Luiz Fernando [UNESP] (Univ Federal Vicosa, 2017)
The intensity and frequency of drought periods has increased according to climate change predictions. The fast overcome and recovery are important adaptive features for plant species found in regions presenting water shortage periods. Copaifera langsdorffii is a neotropical species that has developed leaves presenting physiological mechanisms and morphological adaptations that allow its survival under seasonal water stress. We aimed in this work to observe substantial physiological responses for water saving and damage representative to the photochemical reaction after exposed plants to water stress and to subsequent recovery. We found in plants mechanisms to control water loss through the lower stomatal conductance, even after rehydration. It goes against the rapid recovery of leaves, indicated by the relative water content values restored to previously unstressed plants. Stomatal conductance was the only variable presenting high plasticity index. In photochemical activity, the species presented higher photochemical quenching, electron transport rate and effective quantum yield of photosystem II when they were subjected to rehydration after water stress period. Our results suggest that C. langsdorffii presented rapid rehydration and higher photochemical efficiency even after water restriction. These data demonstrate that this species can be used as a model for physiological studies due to the adjustment developed in response to different environmental schemes.
Keywords: Chlorophyll fluorescence; Water relations; Photosystem II